Hakikat "Ada” dalam Banjir di Mauponggo Telaah Ontologis Atas Kerapuhan Eksistensi Manusia di Hadapan Alam (Jurnal Riset Rumpun Agama dan Filsafat, 2026)
The flood disaster the struct Mauponggo, Flores, Est Nusa tenggara, not only caused infrastructural destruction, loss of life and social trauma, but also revealed a deeper philosophical dimension of human existence. From an ontological prespective, a disaster is not merely a natural occurrence but a moment of disclosure that unvieils the existential fragility of human beings in the faceof natural forces beyond rational, technological, and social control. Onology, as a branch of metaphysics that explores the nature of being, understands humans as beings whose existence is inseparable from space, time, and limitation. Trough a reflective and literature based approach, this study examines the Mauponggo flood as an existential event that exposes the ontological condition of humanity, drawing particularly on Martin Heidegger’s concepts of being toward death and being in the world. The finding show that disaster reveals humans as finite and vulnerable beings who remain open to relationships with nature, others, and the transcendent. This study affirms that an ontological prespective on disaster not only enriches academic discussions on the philosophy of disaster but also holds practical signifincace. The awareness of existential fragility encourages social solidarity, ecological ethics, and deeper transcendental reflection. Thus, this work contributes to developing more reflective and meaningful humanitarian and sustainability responses rooted in a philosophical understanding of human existence and its place in the world.